Saccade and Fixation Eye Movements During Walking in People With Mild Traumatic Brain Injury - Lirani-Silva, Ellen; Stuart, Samuel; Parrington, Lucy; Campbell, Kody; King, Laurie (Frontiers in Bioengineering and Biotechnology, 2021)
Background: Clinical and laboratory assessment of people with mild traumatic brain injury (mTBI) indicate impairments in eye movements. These tests are typically done in a static, seated position. Recently, the use of mobile eye-tracking systems has been proposed to quantify subtle deficits in eye movements and visual sampling during different tasks. However, the impact of mTBI on eye movements during functional tasks such as walking remains unknown. Objective: Evaluate differences in eye-tracking measures collected during gait between healthy controls (HC) and patients in the sub-acute stages of mTBI recovery and to determine if there are associations between eye-tracking measures and gait speed. Methods: Thirty-seven HC participants and 67individuals with mTBI were instructed to walk back and forth over 10-meters, at a comfortable self-selected speed. A single 1-minute trial was performed. Eye-tracking measures were recorded using a mobile eye-tracking system (head-mounted infra-red Tobbii Pro Glasses 2, 100 Hz, Tobii Technology Inc., VA, USA). Eye-tracking measures included saccadic (frequency, mean and peak velocity, duration and distance) and fixation measurements (frequency and duration). Gait was assessed using six inertial sensors (both feet, sternum, right wrist, lumbar vertebrae and the forehead) and gait velocity was selected as the primary outcome. general linear model was used to compare the groups and association between gait and eye-tracking outcomes were explored using partial correlations. Results: Individuals with mTBI showed significantly reduced saccadic frequency (p = 0.016), duration (p = 0.028) and peak velocity (p = 0.032) compared to the HC group. No significant differences between groups were observed for the saccade distance, fixation measures and gait velocity (p > 0.05). A positive correlation was observed between saccade duration and gait velocity only for participants with mTBI (p=0.025). Conclusion: Findings suggest impaired saccadic eye movement, but not fixations, during walking in individuals with mTBI. These findings have implications in real-world function including return to sport for athletes and return to duty for military service members. Future research should investigate whether or not saccade outcomes are influenced by the time after the trauma and rehabilitation.